Negative irrealis clauses in Malay/Indonesian and Sri Lankan Malay infinitives - Slomanson, Peter (UI Scholars Hub, 2021)
This article concerns establishing a plausible connection between the word jang(an) in colloquial Malay varieties and jang-, a form which negates infinitives, in the diasporic contact variety Sri Lankan Malay. The principal claim is that jang(an) marks irrealis modality in Southeast Asian Malay varieties, in which it is frequently (optionally) deployed in negative subjunctive-like embedded clauses. A related claim, dependent on the first of the two, is that the irrealis interpretation conveyed by jang(an) makes it a semantically plausible bridge from a Malay grammar with clausal symmetry to the grammar of Sri Lankan Malay. In Sri Lankan Malay, embedded clauses are frequently non-finite, with infinitives similarly conveying irrealis meaning. Sri Lankan Malay jang- is in complementary distribution with the affirmative infinitival prefix me-, which is also derived from a marker of irrealis modality (mau) in colloquial Southeast Asian Malay varieties.